2017
DOI: 10.5888/pcd14.160605
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention Interventions in US Public Schools: Are Schools Using Programs That Promote Weight Stigma?

Abstract: IntroductionDespite substantial research on school-based obesity prevention programs, it is unclear how widely they are disseminated. It is also unknown whether schools use obesity programs that inadvertently promote weight stigma or disordered weight-control behaviors.MethodsIn spring 2016, we distributed an online survey about school wellness programming to a simple random sample of US public school administrators (N = 247 respondents; 10.3% response rate). We analyzed survey responses and conducted immersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Finally, schools should carefully evaluate the weight‐related messages relayed in health curricula. Most health programs in US public schools focus on “obesity prevention” in ways that exacerbate weight stigma . In particular, curricula that emphasize the importance of personal responsibility in weight maintenance indirectly can blame youth with overweight and obesity for their high weight .…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, schools should carefully evaluate the weight‐related messages relayed in health curricula. Most health programs in US public schools focus on “obesity prevention” in ways that exacerbate weight stigma . In particular, curricula that emphasize the importance of personal responsibility in weight maintenance indirectly can blame youth with overweight and obesity for their high weight .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Most health programs in US public schools focus on “obesity prevention” in ways that exacerbate weight stigma . In particular, curricula that emphasize the importance of personal responsibility in weight maintenance indirectly can blame youth with overweight and obesity for their high weight . Unlike obesity prevention programs, those that focus on healthy eating and physical activity for all students are likely to be more effective in promoting health and well‐being .…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…It required annual body mass index (BMI) screenings for all public school students, elimination of elementary school students’ access to vending machines, and creation of physical education and nutrition standards via district physical activity and nutrition committees along with input from a Child Health Advisory committee. 91 , 92 A study published in 2018 assessing the effectiveness of this policy concluded that it was very unlikely that the Arkansas Act was having an impact on preventing adolescent overweight and obesity. 93 …”
Section: School-based Interventionsmentioning
confidence: 99%
“…Despite its recognized value and advantages, not all school programs targeting health have shown to be effective. For instance, previous literature highlights how programs not founded on strong evidence may have a negative impact on students’ cognitive and physical assets [ 6 ]. A review of physical education interventions showed that only half of the studies obtained significantly positive results [ 7 ].…”
Section: Introductionmentioning
confidence: 99%